School reorganization reforms: The case of school networks in Colombia - Gregory Elacqua; Fabio Sánchez Torres; Humberto Santos (Inter-American Development Bank (IDB), 2019)
To contribute to the debate about the reorganization of the public-school supply, in this paper we analyze a reform introduced in Colombia in 2001 that merged several independent small schools into a single educational institution, with the same name, administration, educational project and school principal. Specifically, we estimate the differences in student achievement and measures of teacher characteristics and technological infrastructure between school sites belonging to a multi-site institution with single-site schools. Our results suggest that there are no differences in standardized test scores, but at the same time, we found that school sites belonging to multi-site schools, especially those in larger networks (more than 6 sites) and located far away from the main site of the school, tend to have younger teachers that earn lower salaries and are more likely to have a temporary contract. We also find evidence that more isolated sites from large-sized schools have less of a probability to have access to the Internet and a computer room than single-site schools. From the point of view of public policy, these results provide suggestions of potential reforms that should be implemented to increase cooperation between sites within the same school.
Keywords: I21; I24; I28; 330; school reorganization; Colombia; educational achievement